2016
DOI: 10.3823/2078
|View full text |Cite
|
Sign up to set email alerts
|

Application and Validation of Breastfeeding Self-Efficacy Scale – Short Form (BSES - SF) in Adolescent Mothers

Abstract: Objectives: Check the reliability and validity of Breastfeeding SelfEfficacy Scale -Short Form (BSES-SF) in Brazilian adolecent puerperal mothers who have recently given birth; and evaluate the association of scores of the BSES-SF with the socioeconomic and obstetric variables of the studied population.Methods: Methodological and quantitative study developed in a public maternity in Fortaleza involving 79 adolescent puerperal mothers. The BSES-SF and a form with socioeconomic and obstetric variables were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
5
1
2
Order By: Relevance
“…This aspect is considered a protective factor (14) . In disagreement with the findings of the present article, a study carried out with 79 mothers in a public maternity hospital in Fortaleza--CE, Brazil, showed a significant association of maternal self-efficacy in breastfeeding with the educational level (p=0.032) (15) .…”
Section: Discussioncontrasting
confidence: 99%
“…This aspect is considered a protective factor (14) . In disagreement with the findings of the present article, a study carried out with 79 mothers in a public maternity hospital in Fortaleza--CE, Brazil, showed a significant association of maternal self-efficacy in breastfeeding with the educational level (p=0.032) (15) .…”
Section: Discussioncontrasting
confidence: 99%
“…Os resultados se juntam a estudos prévios (14)(15)(16)(17)(18)(19)(20) que já haviam mostrado a influência da autoconfiança materna sobre a duração do AM. Na África, Canadá e Japão, estudos também apontam que níveis mais elevados de autoeficácia na amamentação preveem uma duração mais longa e um padrão mais exclusivo de amamentação (17)(18)(19) .…”
Section: Discussionunclassified
“…No Brasil, nas regiões Nordeste e Sudeste, pesquisas mostram resultados semelhantes a estudos realizados em outros países, em que mães de crianças que eram amamentadas exclusivamente com leite materno apresentaram médias dos escores de autoeficácia na amamentação mais elevadas, tanto no pré-natal como no puerpério, e assim reduzindo as taxas de desmame precoce (15,16,20) . Porém há estudos discordantes: dois estudos brasileiros, que não encontraram relação entre autoeficácia na amamentação e duração do aleitamento materno (13,21) .…”
Section: Discussionunclassified
“…The study by Guimarães et al showed that most adult and adolescent mothers had a high level of self-efficacy (54%) and no significant differences were observed between the two age groups [2]. However, the results of a study showed that breastfeeding self-efficacy was lower in young mothers than in adult mothers [6]. Another study reported that the onset of breastfeeding and the longer duration of breastfeeding is more prevalent among older mothers than among younger mothers [2].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…By promoting breastfeeding, the mortality rate of children under 5 years of age in the world can be reduced to less than 13% [6]. Despite the recommendation of the WHO, exclusive breastfeeding in children under 6 months is from 7.7% to 60.4% and the average duration of breastfeeding is from 6.3 to 21.7 months [7].…”
Section: Introductionmentioning
confidence: 99%